Quality of evidence supporting the role of non-steroidal anti-inflammatory drugs for the treatment of anxious depression: a protocol for an overview of systematic reviews and meta-analyses - Jianmin Liu; Hongshuo Shi; Chengda Dong; Zhaojun Yan; Guomin Si (BMJ Open)
Introduction There have been several studies showing the effectiveness of non-steroidal anti-inflammatory drugs (NSAIDs) for anxious depression. We aimed to summarise the evidence and evaluate the methodological quality regarding the effectiveness and safety of NSAIDs for anxious depression from systematic reviews/meta-analyses (SRs/MAs).Methods and analysis Two researchers searched seven databases for SRs/MAs, which are randomised controlled trials on NSAIDs for anxious depression. Two investigators used the Assessment System for Evaluating Methodological Quality 2, the Risk of Bias in Systematic reviews tool, the list of preferred reporting items for SRs/MAs and the Grading of Recommendations, Assessment, Development and Evaluation system to assess the included SRs/MAs.Ethics and dissemination The findings of the study will be disseminated through peer-reviewed journals, and national and international conference presentations.